2021
DOI: 10.1080/01559982.2021.1975616
|View full text |Cite
|
Sign up to set email alerts
|

Do CEO social connections promote corporate malpractices? Evidence from classification shifting

Abstract: This paper examines the effect of CEOs' external social connections with other executives and directors on classification shifting, a widespread malpractice that inflates core earnings by altering the presentation of income statement line items without affecting bottom-line income. Using a sample of 995 UK listed firms in the period 2005 to 2016 and relying on the assumptions of social capital theory and the rent-extraction perspective, we find that CEOs with a larger number of external connections are more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Khaki et al (2021) showed that the social pressures of the stakeholders have a positive and significant effect on aggressive financial reporting. Malikov and Gaia (2021) find that find that CEOs with a larger number of external connections are more likely to engage in classification shifting. Barani et al (2022) show that the obedience social pressure has positive and significant effect on incorrect decisions in providing financial reporting.…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 83%
“…Khaki et al (2021) showed that the social pressures of the stakeholders have a positive and significant effect on aggressive financial reporting. Malikov and Gaia (2021) find that find that CEOs with a larger number of external connections are more likely to engage in classification shifting. Barani et al (2022) show that the obedience social pressure has positive and significant effect on incorrect decisions in providing financial reporting.…”
Section: Related Literature and Hypotheses Developmentmentioning
confidence: 83%
“…We control for the degree of financial leverage because levered firms engaged in expense shifting and revenue shifting to avoid violation of debt covenants (Fan et al, 2019; Malikov et al, 2019). Similarly, following many prior studies (for instance, Malikov and Gaia, 2021; Zalata and Roberts, 2016), we control for profitability as a scale measure. We control for the firm’s age because young firms are highly incentivized to favorable influence their capital providers toward their operational efficiency through earnings management.…”
Section: Methodsmentioning
confidence: 99%
“…The accumulation of social capital can bring capital, talent, knowledge, and other valuable elements to enterprises, thereby encouraging proactive risk‐taking activities (Abernethy et al., 2019). A CEO's wealth of social capital enhances their ability to integrate resources, which, in turn, can stimulate risk‐taking activities (Malikov & Gaia, 2021). The richer a CEO's social capital, the stronger their capacity for resource integration, thus promoting risk‐taking activities.…”
Section: Hypotheses Developmentmentioning
confidence: 99%